Per una nuova identità di psicoterapeuta. La scuola Bios Psychè - De Simone, Gianfranco (Il sogno della farfalla, 2021)
This article introduces the issue of the journal which collects the contributions of the speakers who took part in the first psychotherapeutic training session organized by the School of dynamic psychotherapy Bios Psychè, on the topic of supervision and diagnosis which was attended by about one hundred psychotherapists. The author analyses the training program of the school which has been based on Massimo Fagioli’s innovative ideas and clinical theoretical model that have always put in the foreground the research for word’s truthfulness and the social value of psychotherapy.